INSPIRATION IN SURPRISING PLACES: SEARCHING FOR A CIVIC DIMENSION IN FINANCIAL LITERACY. Issue 2 (3rd March 2020) - Tamir, Eran; Davidson, Roei
ABSTRACT: Establishing Financial Literacy (FL) programs for K-12 students is an emerging concern for policymakers worldwide. Such programs esteem the market a preferred arena for economic decision-making than the civic arena. In parallel, media organizations in many capitalist economies are devoting increasing resources to popular coverage of finance, which could be regarded as an informal form of FL. We build on the distinction between episodic and thematic framing to consider two divergent approaches to FL in Israel: one developed by a non-profit for use in public education and the other developed by a commercial news organization for broader dissemination. We found that the commercial news organization blended episodic and thematic framing to contextualize financial products and institutions temporally and spatially, uncovering the political processes that shape the economic landscape. This paper argues that such a civic and critical approach to financial literacy hails students as citizens with the capacity to reform and re-imagine finance, rather than act solely as passive consumers.